Phenotypic plasticity of coffee trees in an altitudinal gradient of the Frailesca region of Chiapas - Romero José, Emanuel; Rodríguez Larramendi, Luis Alfredo; Salas Marina, Miguel Ángel; Gordillo Curiel, Alder (Revista Mexicana de Ciencias Agrícolas, 2024)
The cultivation of coffee in agroecosystems atypical for this species affects its growth due to the effect of climate, mainly temperature and solar radiation. In 2021, variations in the microclimate, functional traits, and phenotypic plasticity of the coffee tree were studied in two altitudinal gradients of the Frailesca region, Chiapas. Plant height, stem diameter, length of orthotropic internodes, branches per plant, length of plagiotropic branches, total nodes per plant, leaves per plant, specific leaf mass, and specific leaf area were recorded in two shaded coffee plantations located at 600 and 1 000 masl. Diurnal variations in photosynthetically active radiation, air temperature, and relative humidity were recorded. Photosynthetically active radiation, air temperature, and leaves per plant were greater at 1 000 masl due to the greater amount of shade existing in the coffee plantation located at 600 masl. The photosynthetically active and incident radiation at both altitudes was below the points of light compensation and saturation reported for this crop, while air temperature, leaves per plant, and RH were outside the recommended range for the coffee tree. Stem diameter, branches per plant, length of plagiotropic branches, specific leaf mass, and specific leaf area were higher in coffee trees grown at 1 000 masl. It is concluded that the Costa Rica 95 variety showed phenotypic plasticity in response to the altitudinal gradient reflected in increases in the relative distance plasticity index of stem diameter and specific leaf mass.
Keywords: Coffea arabica L.; functional traits; microclimate